Renewed Perspectives on the Deep Roots and Broad Distribution of Animal Consciousness - Irwin, Louis N. (Frontiers in Systems Neuroscience, 2020)
The vast majority of neurobiologists have long abandoned the Cartesian view of non-human animals as unconscious automatons – acknowledging instead the high likelihood that mammals and birds have mental experiences akin to subjective consciousness. Several lines of evidence are now extending those limits to all vertebrates and even some invertebrates, though graded in degrees as argued originally by Darwin, correlated with the complexity of the animal’s brain. A principal argument for this view is that the function of consciousness is to promote the survival of an animal – especially one actively moving about -- in the face of dynamic changes and real-time contingencies. Cognitive ecologists point to the unique features of each animal’s environment and the specific behavioral capabilities that different environments invoke, thereby suggesting that consciousness must take on a great variety of forms, many of which differ substantially from human subjective experience.